A healthy lifestyle pattern and the risk of symptomatic gallstone disease: results from 2 prospective cohort studies. Issue 3 (2nd July 2020) - Wirth, Janine; Joshi, Amit D; Song, Mingyang; Lee, Dong Hoon; Tabung, Fred K; Fung, Teresa T; Chan, Andrew T; Weikert, Cornelia; Leitzmann, Michael; Willett, Walter C; Giovannucci, Edward; Wu, Kana
ABSTRACT: Background: Symptomatic gallstones cause high financial and disease burden for public health systems. The combined role of diet and other lifestyle factors has not been studied so far. Objectives: We aimed to investigate the association between an a priori defined healthy lifestyle score (HLS, including healthy diet, moderate alcohol and regular coffee intakes, never smoking, physical activity, and normal weight) and the risk of symptomatic gallstone disease, and to estimate the proportion of cases potentially preventable by lifestyle modification. Methods: We followed 60, 768 women from the Nurses' Health Study (NHS) and 40, 744 men from the Health Professionals Follow-up Study (HPFS), both ongoing prospective cohort studies, from baseline (1986) until 2012. Symptomatic gallstone disease was self-reported and validated by review of medical records. The association between the HLS and the risk of symptomatic gallstone disease was investigated using Cox proportional hazards regression. Results: During 1, 156, 079 and 769, 287 person-years of follow-up, respectively, 6946 women and 2513 men reported symptomatic gallstone disease. Comparing 6 with 0 points of the HLS, the multivariable HR of symptomatic gallstone disease was 0.26 (95% CI: 0.15, 0.45) for women, and 0.17 (95% CI: 0.07, 0.43) for men. For individual lifestyle factors, multivariable and mutually adjusted partial population attributable risks (women and men) were 33% and 23% for BMI <25 kg/m 2, 10% and 18% for ≥2 cups of coffee per day, 13% and 7% for moderate alcohol intake, 8% and 11% for a high Alternate Healthy Eating Index 2010, 9% and 5% for being physically active, and 1% and 5% for never smoking. The full population attributable risk percentage for all factors combined was 62% and 74%, respectively. Conclusions: Findings from these large prospective studies indicate that adopting a healthy lifestyle, especially maintaining a healthy weight, can help to prevent a considerable proportion of symptomatic gallstone diseases.